Starbucks’ marketing communications strategy on Twitter - Viriya Taecharungroj (2018)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. Many scholars have found that social media are extraordinarily useful platforms for marketers to engage their stakeholders. Much research has developed frameworks for and proposed empirical guidelines on how brands should communicate and interact with audiences on social media platforms. However, a comprehensive study that is based on a successful and reputable brand is still lacking. The objective of this research was to categorise the types of content used by one of the most admired brands in the world, Starbucks, and evaluate its effectiveness on Twitter. In total, the author studied 565 tweets and retweets and 1392 replies. This research found that Starbucks’ marketing communications strategy includes three types of original and retweeted content: information-sharing, emotion-evoking, and action-inducing content. The author also found six types of replies: information, Apology and suppot, positive comment, question and enquiry, chit-chat, and gratitude. To be successful on the social media platforms, this research suggests that brands should use various types of content, focus on visual content, and prepare for and manage customer interactions appropriately. The findings present useful and practical information for brands that seek to engage audiences using an inexpensive but compelling marketing communications strategy on social media.